Congenital erosive and vesicular dermatosis with reticulated scarring in twins, associated with oesophageal atresia. (2nd February 2022) - Nemazee, Leila; Cuddy, Laura; Clayton, Timothy H.
Abstract : This is a case of twins who had a rarely seen diagnosis of congenital erosive and vesicular dermatosis. This report includes a description of the case and discussion around the topic. Click https://www.wileyhealthlearning.com/#/online-courses/2fd90f74-cd50-4ae4-aeef-61d902f63ec0 for the corresponding questions to this CME article.